PARSING THROUGH BODO MYTHS: ITS REFLECTION AND SIGNIFICANCE IN SOCIETY - Narzary, Hargouri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Throughout the inhabited world, in all ages and under every situation, the myths of man have flourished. It is a heritage shared by all humans and an inherent as well as a crucial part of culture since antiquity. For members of any society, primitive/folk or modern myths seem to hold timeless importance and veneration; they have been a living inspiration of whatever else may have appeared out of the human activity and mind. In a similar view, the Bodos possess a distinct mythological tradition that shows excellent varieties. It goes without saying that myths, i.e., mwdai daodwi ni solo in the Bodo society are not just human imagination or creation, but represent their actual human life. Myths form a valued part of their sacred circle of life and it serves as a vehicle of emotional introspection and release. In this paper, an earnest attempt will be made to explore the reflection and significance of myths in their society.